2016
DOI: 10.1080/09553002.2016.1254834
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect of green tea and grape seed extracts mixture on gamma irradiation induced immune suppression in male albino rats

Abstract: GTE and GSE mixture is a good radioprotector and immune modulator compound, indicating its possible use as an adjuvant during radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Some assays were also conducted in the BJ human skin fibroblast cell line in order to confirm our observation in keratinocytes. The inflammatory process is a key consequence after gamma radiation exposure, which is characterized by the increased levels of pro-inflammatory cytokines, including IL-6, TNF-α, and IL-1β [75,76]. Our study detected the enhancement in these inflammatory cytokines in cells and mice after gamma radiation exposure.…”
Section: Discussionsupporting
confidence: 51%
“…Some assays were also conducted in the BJ human skin fibroblast cell line in order to confirm our observation in keratinocytes. The inflammatory process is a key consequence after gamma radiation exposure, which is characterized by the increased levels of pro-inflammatory cytokines, including IL-6, TNF-α, and IL-1β [75,76]. Our study detected the enhancement in these inflammatory cytokines in cells and mice after gamma radiation exposure.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, Ahmed et al demonstrated that green tea by-products (contain 9.22% moisture, 20.1% crude protein, 2.91% crude fat, 18.2% crude fiber, 4.88% crude ash, 33.2% nitrogen-free extract, and 11.6% catechins) supplemented at the ratio of 0.5%, 1.0%, or 2.0% in diet positively modulated the proliferation of immune cells in goats in a linear mode [102]. On the other hand, tea can interact with other natural products to regulate the immune response [50,103]. In one study, the mixture of green tea and grape seed extract (100: 200 mg/kg BW) relieved the immune suppression induced by γ-irradiation in male rats, showing radioprotective effect [103].…”
Section: Immuno-regulative Activity In Vivomentioning
confidence: 99%
“…On the other hand, tea can interact with other natural products to regulate the immune response [50,103]. In one study, the mixture of green tea and grape seed extract (100: 200 mg/kg BW) relieved the immune suppression induced by γ-irradiation in male rats, showing radioprotective effect [103]. In another study, the combined administration of green tea Se-TPS and Huo-ji polysaccharides (1:1, 300 mg/kg BW) exerted synergistic effects on improving the immune function in mice [50].…”
Section: Immuno-regulative Activity In Vivomentioning
confidence: 99%
“…Grape seed extract (GSE) was prepared according to Ahn et al and El-Desouky et al [44,45]. Grape seeds (GS) were dried at 50°C for 3 days in drying oven.…”
Section: Green Tea and Grape Seed Extracts Preparationmentioning
confidence: 99%
“…The obtained extracts were mixed to prepare GTE-GSE mixture with a ratio of 1:2 (100 mg GTE: 200 mg GSE). The mixture was determined previously by LC/DAD/MS HPLC and kept frozen at -20°C until further use [43,45].…”
Section: Green Tea and Grape Seed Extracts Preparationmentioning
confidence: 99%